KAPASITAS MASYARAKAT DALAM PENGELOLAAN SAMPAH KOTA (Studi Masyarakat Jakarta, Tangerang, Bekasi, Depok) - Widodo, Lestario; Susanto, Joko Prayitno (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Principally, solid waste management is all activities of solid waste handling, from thepoint sources until the final disposal. Up to know solid waste management in urban areais still a complex problem, either from social, management, and technology aspects.The other problem of solid waste management is due to the people behaviour, whichis mostly still unaware. Social capacity is another word social capital means a socialcondition that a lot of citizens participate the process of decision making or policymaking and cooperation with government. The role of community in this system is onlyin paying the monthly fee. So that people still fully gave the solid waste managementsystem in to the government. There is no indication of solid waste sparation by thepeople them selves.